A comprehensive analysis of vitamin A deficiency in China from 1990 to 2021, examining temporal trends and demographic influences - Du, Yue; Jiang, Feng; Lei, Tianyao; Juan, Chenxia; Mao, Yan (Frontiers in Nutrition, 2025)
BackgroundVitamin A deficiency (VAD) remains a critical public health burden in China, particularly affecting children and reproductive-age women. A comprehensive analysis of its long-term trends is essential for guiding nutritional interventions.MethodsUtilizing data from the Global Burden of Disease (GBD) 2021 study covering 1990 to 2021, we examined age-standardized incidence, prevalence, disability-adjusted life years (DALYs), and sociodemographic factors influencing VAD in China. Joinpoint regression detected temporal inflection points, and Bayesian age-period-cohort (BAPC) modeling forecasted incidence up to 2040. Frontier analysis correlated burden with the socio-demographic Index (SDI) across 204 countries.ResultsIn 2021, China reported 23.19 million new VAD cases, with higher age-standardized incidence in females (2,094.3/100,000) versus males (1,821.07/100,000). A bimodal age distribution peaked in children (<14 years, male-predominant DALYs) and young adults (20–34 years, female-predominant incidence). From 1990–2021, age-standardized rates declined by 81.2% (incidence) and 81.2% (prevalence), surpassing global reductions. Critically, a 2013 inflection point reversed sex disparities: male burden exceeded females before 2013, but female rates dominated thereafter. Sub-Saharan Africa experienced the highest burden globally, with a negative correlation between SDI and VAD incidence (R2 = 0.72, p < 0.001). BAPC projections indicate persistent declines through 2040, but males will retain higher incidence than females.ConclusionDespite substantial progress, VAD persists with evolving sex-age disparities. The 2013 sex burden reversal and dual vulnerability of children/young adults necessitate sex-stratified interventions. Integration of supplementation programs with socioeconomic development is vital for eliminating VAD in China and high-burden regions.